Persistent Patterns: Moyaert, the Moriscos and Muslims in Europe - Nawaz, Amina (Campus der Theologien, 2025)
In her most recent book, Marianne Moyaert points to historical patterns in the establishment of Christian normativity. This article engages with and applies Moyaert’s frame of religionization to explore European tensions with Islam and Muslims. The article highlights comparisons between the historical experiences of early modern Spain and the Moriscos (forcibly baptized Muslim communities) and contemporary Muslim communities in Europe. In so doing, it engages Moyaert’s idea of patterns of religionization by demonstrating the consistent methods, discourses and policies of ›religious othering‹ that often persist in contemporary European discussions of Islam and Muslims. The presence of these patterns poses a challenge to liberal thought and policies and demands a more robust theorization/application of notions of ›tolerance‹.